Analisis Penetapan Harga Pokok Produksi Kacang Disco di UD Kecak Mama - SENA, NI MADE ESTER WIDYANTI; DEWI, RATNA KOMALA; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Analysis Determining The Cost Of Production Disco Beans at UD Kecak Mama The COVID-19 pandemic conditions, as well as the business's location, determine UD Kecak Mama business competitiveness. To keep this competition at bay, competitive pricing might be used. It will necessitate a more exact method. The purpose of this research is to determine the cost of production with the UD Kecak Mama method, the cost of production with the full costing method, and the difference between the two. The method used is full costing. According to the findings of the study, UD Kecak Mama's computation calculates the cost of production solely by varying the packing size, so that the results were Rp. 9.738,00 per pack of 200 gr and Rp. 19.475,00 per pack of 400 gr. The full costing method determines a unique production cost for each taste and packaging variations. The cost of production obtained ranges from Rp. 10.108,00 to 11.020,00 for per pack of 200 gr, and Rp. 20.216,00 to Rp. 22.040,00 for per pack of 400 gr. The difference between these two ways is that the production costs for each disco bean flavored variant quite far in all that different. As a result, the full costing method's cost of production is still lower than the selling price, and UD Kecak Mama should employ the full costing method for its cost of production because it has meticulously examined the costs.